PENATALAKSANAAN RADIOTERAPI KANKER PAYUDARA TEKNIK IMRT - Ira Wulandari; Nursama Heru Apriantoro; Sriyatun Sriyatun; Moh Haris (Perhimpunan Radiografer Indonesia (PARI), 2023)
ABSTRACT Background: Radioteraphy is one of treatment theraphy to cancer. Radiation techniques in the breast cancer at Cancer Dharmais Hospital can be done with several techniques such as 3 Dimensional Conformal Radiotherapy (3DCRT), Intensity Modulated Radiotherapy (IMRT), Volumetric Modulated Arch Therapy (VMAT) depending on the planning by the radiation oncologist based on the stage and purpose of radiation. The purpose this research is to evaluation the treatment of radiotherapy using the IMRT breast cancer at Cancer Dharmais Hospital. Methods: The type of the research is used qualitative with a case study approarch of breast cancer using IMRT technique in a 47 years old female with IIa stage, curative therapy with fraksination 25x2 Gray (Gy). Results: The treatment of radioteraphy to breast cancer with the IMRT technique was chosen taking into account the low stage of the cancer, the location of the cancer that is difficult to reach when using the 3DCRT technique, the purpose of giving radiation that is curative, and the large number of Organ At Risk (OARs) must be protected. Conclusions: The treatment of radiotherapy to breast cancer using the IMRT tecnique at Cancer Dharmais Hospital is done through in several stages, such as : consulting a Radiation Oncologist at the Radiotherapy Polyclinic, do a simulation on the Computer Tomograpy (CT) simulator, calculated dose at Treatment Planning System (TPS), Process of geometry verification is done before the treatment and then continued with the process of treatment in the linac room.